2011
DOI: 10.5101/nbe.v3i1.p53-56
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetic Profile of Freeze-dried Cyclosporine A-Eudragit S100 Nanoparticle Formulation in Dogs

Abstract: The pharmacokinetic profile of freeze-dried cyclosporine A-Eudragit S100 nanoparticles (CyA-S100-NP)was studied with a random two-way crossover study in dogs. The drug blood concentration was determined by internal standard HPLC method after oral administration of CyA-S100-NP and Neoral. Pharmacokinetics parameters were calculated by 3P97 program. The concentration-time data were fitted as a two-compartment open model. The AUC of CyA-S100-NP was higher than that of Neoral(P<0.05), while the CL significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This material is the poly(methyl methacrylate (MMA)-co-methacrylic acid (MAA)) copolymer or P(MMA-co-MAA), in a MMA:MAA molar ratio of 0.64:0.36, which is similar to Eudragit S100 (ES 100), a polymer widely used in the elaboration of drug-loaded pills due to its water solubility at pH >7 [24]. Although the preparation of ES 100 NP with mean diameters ranging from 50 to 700 nm, loaded with different drugs, have been documented [25][26][27][28][29][30][31], obtaining NP from a copolymer similar to ES 100 loaded with drugs and with diameters less than 50 nm has only been reported by our group [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…This material is the poly(methyl methacrylate (MMA)-co-methacrylic acid (MAA)) copolymer or P(MMA-co-MAA), in a MMA:MAA molar ratio of 0.64:0.36, which is similar to Eudragit S100 (ES 100), a polymer widely used in the elaboration of drug-loaded pills due to its water solubility at pH >7 [24]. Although the preparation of ES 100 NP with mean diameters ranging from 50 to 700 nm, loaded with different drugs, have been documented [25][26][27][28][29][30][31], obtaining NP from a copolymer similar to ES 100 loaded with drugs and with diameters less than 50 nm has only been reported by our group [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The processes involved usually include the dissolution of a drug-copolymer mixture in a suitable solvent which is subsequently evaporated to finally obtain the drug-copolymer particles. These particles usually show mean diameters in the order of hundred nanometers [2][3][4][5][6][7][8][9][10][11]; the exception is the work of Dai et al [3] who obtained drug-loaded nanoparticles with 37 nm in mean diameter, as measured by quasi-elastic light scattering (QLS). It is noticeable that none of these processes include the polymerization step.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that PSS was submerged and dissolved quickly in the medium because PSS is a highly water‐soluble drug. The cumulative release percentage of PSS was approximately 100% in the first 2 h. While enteric PSS‐NP exhibited significant pH sensitivity, there was a slow release in the simulated gastric medium with the cumulative release percentage of PSS below 10% in the first 2 h. Then, the release profile of enteric PSS‐NP in the pH 6.8 medium was significantly different from that in the acid medium and there was a burst release of PSS from enteric nanoparticles in the first 1 h. This burst effect may be caused by the drug absorbed on the surface of nanoparticles . In addition, the dissolution of the Eudragit L30D‐55 in pH 6.8 medium could also lead the burst release of PSS.…”
Section: Resultsmentioning
confidence: 99%